Development of a Small Scale Okro Slicing Machine - Aji, I. S.; Vakaa, J. K.; Madu, M. J.; Suleiman, Z. B.; Yakda, S. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
The technique of slicing Okro using kitchen knife often exposes users to the danger of knife cut and the output of the technique has been found to be low due to the drudgery involved in the process. It was in recognition of the need to reduce drudgery, injury and associated rigors to the user and to enhance quality, hygiene and efficiency in Okro processing that the research of developing a suitable Okro slicing machine was initiated. A simple motorized device was developed for slicing okra using locally available materials which include: bearings, shaft, pulleys, electric motor, cutting blade, rail, bolts and nuts. The slicing mechanism was based on the high shear stress that is generated when a blade edge is brought into contact with fibrous material causing the blade to move in rotary motion and to the direction of the applied force. After coupling and testing the machine, results obtained showed that it takes 3 seconds to slice one Okro using machine while in the case of manual slicing, it takes 8.22 seconds. The device has a slicing efficiency of 66.67%. The machine has shown to enhance processing of okra in small scale industry application. The machine therefore is of great importance to the industries within the country and beyond where preservation of Okro in sliced and dried form is important.